P53 Maternal education and language development at 2 years corrected age in children born very preterm: results from a european population-based cohort study. (3rd September 2019) - Sentenac, MS; Charkaluk, MLC; Johnson, SJ; Zeitlin, JZ
Abstract : Background: In the general population, children from socioeconomically disadvantaged families face higher risks of developmental language delay (DLD). Less research exists on very preterm (VPT) children and results have been contradictory, which may reflect a lesser impact of socioeconomic factors when perinatal risks for delayed development are high. Our objective was to investigate the association of maternal education with DLD at 2 years of age by degree of perinatal risk. Methods: Data come from the Effective Perinatal Intensive Care in Europe (EPICE) cohort, a population-based, prospective cohort study of children born <32 weeks' gestational age (GA) in 2011/2012. Perinatal data were abstracted from medical records and follow-up was conducted using parental questionnaires at 2 years corrected age. Six countries (Belgium, Estonia, France, Italy, Netherlands, UK) used a validated short form MacArthur Developmental Communicative Inventories Checklist (4666 children at inclusion 2990 (64%) followed up); DLD was assessed using 2 outcomes: not yet combining words; expressive vocabulary <10th percentile. Families speaking only other languages at home were excluded. Modified Poisson regression models were used to estimate relative risks (RRs) for DLD for maternal education overall and by perinatal risk (low, moderate, high), classified using GA, small for gestational age (SGA) and severe neonatal morbidities. All analyses were performed using Stata version 15. Results: 2643 VPT children (mean GA 28.8 weeks) were assessed at a median 24 months corrected age. 25.3% were not combining words and almost 40% were <10th percentile for expressive vocabulary. Among children with low perinatal risk (born at 30 and 31 weeks' GA, not SGA, without severe morbidities), risks of DLD were higher when mothers had less than high school versus tertiary education (RR word combination: 2.2 (95% CI: 1.5; 3.3); RR expressive vocabulary: 1.5 (95% CI: 1.1; 2.0)). Among children with higher perinatal risk (lower GA, SGA and severe morbidities), maternal education was not associated with DLD. Conclusion: Maternal education was associated with language development only among VPT children with low perinatal risk. The interaction of social factors with perinatal risk may explain contradictory findings in previous studies.